Metonymy in climate change discourse by King Charles III: A cognitive-linguistic perspective - Kapranov, Oleksandr (Kalbotyra, 2024)
The current British monarch King Charles III is a staunch supporter of climate change mitigation (O’Neill et al. 2013, 413). Whereas he has delivered numerous speeches on climate change both domestically and internationally, currently, however, there are no studies that investigate his speeches on the issue of climate change through a linguistic lens in general and through a cognitive-linguistic prism in particular. Furthermore, there seems to be no published research on such a ubiquitous cognitive-linguistic device as metonymy (Hart 2011) in his speeches on climate change. In order to address the gap in scholarship, the article presents a study that aims to identify the types of metonymy in a corpus of speeches on climate change delivered by King Charles III. The corpus was analysed qualitatively by means of applying a cognitive-linguistic approach to metonymy developed by Radden and Kövecses (1999). The results of the corpus analysis revealed the presence of the following types of metonymy, namely (i) place for a climate change-related event, (ii) place for a climate change-related activity, (iii) place for the government involved in a climate change-related activity, (iv) the generic company name for an actor involved in a climate change-related activity, (v) the specific company name for an actor involved in a climate change-related activity, (vi) the defining property of the category “climate change actor” for the whole category, and (vii) the defining property of the category “climate change goals” for the whole category. The findings are further discussed and illustrated in the article.
Keywords: climate change discourse; cognitive linguistics; conceptual metonymy; King Charles III